PERANCANGAN BUSANA READY-TO-WEAR DELUXE WANITA MENGAPLIKASIKAN SUBBUDAYA GOTIK DENGAN EKSPERIMEN TEXTILE - Kongdoro, Adelene; Enrico, Enrico; Teowarang, Janet (Universitas Ciputra Surabaya, 2024)
Globalization and development of times have triggered the entry of various types of foreign subculturesinto the country, one of which is the Gothic subculture which is widely embraced by the nation's younggeneration, especially in big cities. This subculture is generally associated with things that tend to bedepressive and contain elements of rebellion which cause negative societal stigma and stereotypestowards people who are part of this subculture, thus creating limitations in accessibility. The design, which discusses the application of gothic subculture into deluxe ready-to-wear clothing with textile artexperiments, was carried out with the aim of showing the artistic and aesthetic side of gothic style tocounter the negative views of the general public and the limited accessibility of gothic subculture usingqualitative research methods by collecting data from 6 experts and 12 extreme users. The design method used is Design Thinking which consists of five stages, namely empathize, define, ideate, prototype, and testing which produces five final designs by applying textile art and trend analysis in collections inspired by the Gothic subculture. It is hoped that this design can be a mean of self-expression so that stereotypes and negative views of the gothic subculture are not the focus of society and can expand the accessibility of this style to the general public.